A social marketer, a geographer, and an engineer walk into a bar: Reflections on energy + Illawarra and undertaking interdisciplinary projects. Issue 4 (9th October 2017) - Gordon, Ross; Waitt, Gordon; Cooper, Paul
Abstract : Purpose: This paper aims to contribute to contemporary debates about interdisciplinarity and social marketing by presenting the critical reflections of a social marketer, a human geographer and an engineer on working across disciplines in an Australian community energy efficiency intervention – Energy + Illawarra. The paper also aims to identify challenges, practicalities and learning that emerge from collaborating on interdisciplinary projects. It also aims to provide some suggestions and guidelines for researchers in the interdisciplinary space. Design/methodology/approach: The paper uses a case study approach and presents the critical reflections of a social marketer, a human geographer and an engineer on working together on the Energy + Illawarra project – a community energy efficiency social marketing intervention. Findings: Challenges in interdisciplinary projects that are presented by differences in ontology, methodology, language and discourse are identified. The importance of being critically reflexive and openness to alternative perspectives are examined. Concerns over publishing interdisciplinary research are considered. The value of experimenting and developing partnerships through pilot projects is discussed. The potential of leveraging existing synergies and the opportunity to learn from clashes in ontology are also highlighted. Originality/value: This paper contributes to the discussion about being interdisciplinary in social marketing by identifying subjectivities, practicalities and opportunities from collaborating on cross-disciplinary projects. Guidance for researchers on working on interdisciplinary projects offers value for social marketers working in this area.